Mixed use settlements in a metro city: Effects on people & context - Harshitha Alluri (International Journal of Urban Design and Development, 2024)
Mixed-use settlement is a building or a combination of buildings designed to functionally and physically integrate multiple uses such as commercial, institutional, recreational, and other uses along with residential uses. In such spaces, there are more opportunities for pedestrian activities due to the presence of a majority of the daily necessities at near distances. How public spaces are designed plays a significant role in affecting one’s mental state and sense of comfort hence affecting productivity. Mixed-use settlements or spaces are denoted by the ‘live-work-play’ facilities and amenities in a close proximity. This study aims to investigate how mixed-use spaces are used in a metropolitan city by studying three areas from different parts of the city and how people there are affected by the mixed-use setting. Mixed use settelements, incorporating a range of functions and demographics within a single region, are essential to contemporary urban planning. The Old City, which dates back centuries, the planned KPHB Colony, and the quickly expanding Kondapur suburb are the three main locations of Hyderabad, India that are the subject of this study, which explores the dynamics and advantages of mixed-use towns. By means of an extensive methodology that includes field trips, interviews with residents, and a review of the literature, this study seeks to clarify the nuances and effects of mixed-use development in these areas. The results highlight the distinctive qualities and difficulties in every region. Accessibility is hampered in the Old City, which is known for its densely packed medieval architecture, by problems including small streets and a lack of parking, even if the area around famous sites like Charminar is very active. Similar problems with traffic and inadequate parking are present in KPHB Colony, a planned community, however in a more contemporary setting. On the other hand, because of recent projects like flyovers, Kondapur, a rising IT cluster, exhibits better-planned infrastructure. Common features emerge despite contextual differences, such as the requirement for effective transportation alternatives, adequate parking spaces, and infrastructure that is pedestrian-friendly. Because they encourage walking and cycling, mixed-use. This study's conclusion emphasizes how crucial it is for urban planning to incorporate a variety of stakeholders and purposes. It is possible for policymakers to establish lively, sustainable, and livable urban settings that promote the well-being of all citizens by addressing the unique requirements and difficulties of mixed-use settlements.
Keywords: Mixed use settlements; Safety; neighborhoods; streets